Immature cortical responses to auditory stimuli in specific language impairment: evidence from ERPs to rapid tone sequences. - Bishop, D; McArthur, G (2004)
Event-related potentials (ERPs) to tone pairs and single tones were measured for 16 participants with specific language impairment (SLI) and 16 age-matched controls aged from 10 to 19 years The tone pairs were separated by an inter-stimulus interval (ISI) of 20, 50 or 150 ms. The intraclass correlation (ICC) was computed for each participant between the ERP to a single tone and the ERP to the tone pair. A high ICC indicates that the brain response to a tone pair is similar to that for a single tone. ICCs were significantly higher at short than at long ISIs. At 50-ms ISI, ICCs were higher for younger than older participants. Age and ISI interacted with SLI status: ERPs of older participants with SLI differed from age-matched controls, and resembled ERPs of younger controls, consistent with a theory of immature auditory processing in SLI.